Bacterial microbiota of lower gut and bronchi in tuberculosis patients - V. A. Puzanov; O. G. Komissarova; B. V. Nikonenko (Туберкулез и болезни лёгких)
The objective: to study the quantity and variability of bacterial microbiota in lower gut, the prevalence of microorganisms resistant to antibacterial drugs among microorganisms isolated from the bronchi of pulmonary tuberculosis patients receiving chemotherapy.Subjects and methods. Microorganisms of the bacterial microbiota from lower gastrointestinal tract isolated from respiratory tuberculosis patients were studied. 178 patients were examined retrospectively and 53 patients were examined prospectively. Diagnostic specimens obtained from the bronchi/lungs (sputum, bronchoalveolar lavage fluid, aspirate, etc.) of respiratory tuberculosis patients were tested. Bacteriological tests complying with current regulatory documents were used.Results. It was found out that gut microbiota varied in tuberculosis patients of various age groups at different stages of treatment and in addition to that, the microbiota was characterized by certain pronounced manifestations of dysbiosis. In cases when clinically significant microorganisms were isolated from bronchi of respiratory tuberculosis patients, a relatively high prevalence of microorganisms resistant to the most important antibacterial drugs was detected.